Conceptualizing and Measuring Collaboration - Thomson, A. M.; Perry, J. L.; Miller, T. K. (Journal of Public Administration Research and Theory, 2007)
This article conceptualizes and measures collaboration. An empirically validated theory of collaboration, one that can inform both theory and practice, demands a systematic approach to understanding the meaning and measurement of collaboration. We present ﬁndings from a study that develops and tests the construct validity of a multidimensional model of collaboration. Data collected using a mail questionnaire sent to 1382 directors of organizations that participate in a large national service program provides the basis for a higher order conﬁrmatory factor analysis. The model that emerges from this analysis demonstrates an overall close ﬁt with the empirical data and the high, standardized gamma coefﬁcients estimated in the model conﬁrm that ﬁve key dimensions contribute to an overall construct of collaboration. The primary purpose of this research was to stimulate interest in measurement of collaboration and reﬁnement of the model. As such, we present a detailed description of the analytical process, identify areas that affect interpretation of the data (such as possible selection bias), and propose areas for future research. We believe this effort to conceptualize and measure collaboration offers a foundation for further research.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; collaboration / colaboração